Early Quaker Identity from the Perspective of Some Ecclesiastical Anti-Quakers - Roads, Judith (Journal of religion in Europe, 2022)
This empirical case study provides a new approach to the understanding of discursively constructed Quaker identity in the seventeenth century, from the point of view of those opposed to the dissenting Christian movement. This article asks how others may have viewed adherents to the Quaker communities in England. The findings illustrate a range of negative and denigrating discourses that go beyond abstract religious controversy to sow manufactured fear of the Quaker community. Overt and covert linguistic mechanisms used by anti-Quaker writers reveal expressions of emerging moral panic underlying unsubstantiated accusations attacking the minority Quaker community.